Factors Affecting Islamic Social Reporting in the Halal Industry Sector - Budiandru, Mr. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Islamic social reporting is a measure of Islamic-based social performance reporting in each company. Increased disclosure of Islamic social interpretation will influence investor decisions. This study aims to analyze what factors influence the declaration of Islamic corporate social responsibility. The data used is the annual report of companies registered in the halal industry sector from 2013 to 2018 with 44 selected companies. This study uses a random effect model (REM). The analysis results show that the halal lifestyle, profitability, and leverage are significant in disclosing Islamic corporate social responsibility. Implementation of ISR disclosure as a form of accountability is based on principles and philosophies following Islamic Sharia. Therefore, companies must improve their financial performance to enhance corporate social responsibility disclosure quality, which is very important for stakeholders in investing.